The Prevalence and Social Determinants of Hypertension among Adults in Indonesia: A Cross-Sectional Population-Based National Survey - Karl Peltzer (2019)
© 2018 Karl Peltzer and Supa Pengpid. Background. Hypertension is the most significant avoidable cause of morbidity and mortality, yet nationally representative adult data on Indonesia have not been available. The study aimed at assessing the prevalence and determinants of hypertension, including sociodemographic variables, weight status, health behaviour, and psychosocial stress and support risk factors. Methods. The Indonesia Family Life Survey (IFLS-5) interviewed and examined in a national population-based cross-sectional study 29965 individuals aged 18 years and older, mean age 43.3 years (SD=15.3). Blood pressure, body height and weight, dietary behaviour, physical activity, tobacco use, and psychosocial variables were measured. Logistic regression analyses were used to estimate determinants of hypertension by gender. Results. The prevalence of hypertension among study participants was 33.4 % (95 % CI: 32.7-34.0), among males 31.0% (95% CI: 30.2, 31.9), and among females 35.4% (95% CI: 34.6, 36.3). Among hypertensives, 42.9% were aware, 11.5% were treated, and 14.3% were controlled. In fully adjusted analyses, in both men and women, older age, no or elementary education, being overweight or obese, and having visited an outpatients health facility in the past 4 weeks were positively associated hypertension. Significant linear relationships of hypertension were found with age (P for trend <0.001) and body mass index (BMI) (P for trend < 0.001). In addition, among men having quit tobacco use and depressive symptoms were positively associated with hypertension, while current tobacco use was negatively associated with hypertension. Moreover, among women lower subjective economic status was associated with hypertension. Conclusions. The prevalence of hypertension was high and awareness was low, and treatment and control were very low. Significant multilevel public health interventions are urgently needed to improve the diagnosis, treatment, and control of hypertension in Indonesia.